DEKADENSI MORAL BAGI GENERASI MUDA - Luluk Istante (Student Research Journal, 2023)
This paper is a scientific idea that aims to give an idea of the importance or building the character of moral resources, through the internalization or positive values in the implementation of education. This is one way to he able to overcome various issues, especially moral decadence among young people. The method used is literature review. In general, the values that need to be developed and internalized in the implementation of education in Indonesia, among others, religious, mutual cooperation, togetherness, humility, refinement, hospitality, tolerance, so that the unity and unity of the nation can be realized.